Balancing activity and tolerability of neoadjuvant paclitaxel- and docetaxel-based chemotherapy for HER2-positive early stage breast cancer: Sensitivity analysis of randomized trials. Issue 3 (March 2015) - Carbognin, Luisa; Sperduti, Isabella; Nortilli, Rolando; Brunelli, Matteo; Vicentini, Cecilia; Pellini, Francesca; Pollini, Giovanni Paolo; Giannarelli, Diana; Tortora, Giampaolo; Bria, Emilio
Highlights Data were gathered from 15 trials evaluating neoadjuvant paclitaxel and docetaxel for HER2-positive breast cancer. Neoadjuvant paclitaxel determines a slight significant benefit in terms of pCR in comparison with docetaxel. Docetaxel significantly increases severe and febrile neutropenia, while paclitaxel slightly worsens neurotoxicity. Overall, the benefit/risk analysis balancing activity (pCR) with toxicity (severe neutropenia) supports to use paclitaxel. The non-prospective nature of the analysis and its heterogeneity may limit the interpretation of the results.